Microfluidic Device for Monitoring Catalytic Events on Armored Bubbles. Issue 23 (15th July 2022) - Dedovets, Dmytro; Zhang, Shi; Leng, Jacques; Pera‐Titus, Marc
Abstract: A polydimethylsiloxane‐based microfluidic device allows monitoring local oxidation events in organic solvents at the level of an individual air bubble armored with surface‐active low‐surface energy catalytic particles. This new technique permits tunable design of microreactors for gas‐liquid‐solid reactions. Abstract : Microfluidic traps based on polydimethylsiloxane chips to produce, store, and manipulate particle‐stabilized bubbles in organic solvents at elevated temperatures are developed. The traps allow monitoring local oxidation events in organic solvents at the level of an individual air bubble armored with surface‐active low‐surface energy catalytic particles. This new technique permits the tunable design of microreactors for gas‐liquid‐solid reactions.